Determining the character of the Arbaeen procession based on Jung Archetypes - Fozieh Taheri Mina; meisam latifi (Religion & Communication)
AbstractThe growing trend of the Arbaeen March can be analyzed from various cultural , social , political , economic and managerial dimensions. In this research , an attempt is made to analyze this important ritual, which has been repeated and globalized over the past decade, with a psycho - cognitive-managerial approach .The theoretical framework of the research is taken from Jung's model of archetypes, which was later considered by management thinkers in the study of successful trademarks. Our goal is to determine the personality for the Arbaeen procession, by modeling the personality of the creators of this ceremony, which is Imam Hussein and his companions, and based on Jung's archetypes, archetypes that are transnational and are similarly perceived and influenced in different societies .The research method is an in - depth interview and documentary study , and the results of the interviews will be examined using deductive content analysis. The research's innovation in using the Jung framework in a subject beyond the trademark, that is, in a religion, is also religious and spontaneous .Thus , if the archetypes that influence the spread of this religion are discovered, these archetypes can be used in other religious rites and these archetypes can be used in their expansion and dissemination.